The maintenance of fluency following - Lilian, Dina (My University, 2006)
ABSTRACT Rationale: In the early 1990s, the Lidcombe Programme, which is a direct, parentconducted, operant intervention programme for early childhood stuttering, was introduced to therapists. Available data in Australia suggest that the Lidcombe Programme is an effective early communication intervention as it eliminates stuttered speech in the medium and long term and is able to maintain these effects for up to seven years post-treatment (Onslow, Costa & Rue, 1990; Onslow, Andrews & Lincoln, 1994; Lincoln & Onslow, 1997; Jones, Onslow, Harris & Packman, 2000). However, despite the plethora of research in Australia, no South African research appears to have previously been conducted to establish long-term results and maintenance of fluency following the administration of this programme with young children. Purpose: The present study endeavoured to establish long-term results and maintenance of fluency using the Lidcombe Programme with children who stutter. Participants: Nine children were recruited, ranging in age from six to eleven years who had undergone therapy using the Lidcombe Programme during the previous two to six years. The parents of these children also participated in the study. Method: As part of the Lidcombe Programme, the percentage syllables stuttered (%SS) and the severity rating score (SR) were recorded at the time of the assessment and termination of therapy. The researcher evaluated each participant’s speech in two different situations using the measurements of %SS and SR and then compared these scores to the %SS and SR score recorded at the initial assessment and termination of therapy to ascertain whether each participant’s speech had improved, deteriorated or remained consistent. An interview with the child’s parents was also conducted to obtain a qualitative assessment of the parent’s views of their child’s speech since the termination of therapy. Results: The Wilcoxon signed rank test revealed a significant decrease in %SS and SR between pre-treatment scores and scores recorded at the time of the study (p = 0.00195 & p = 0.00195 respectively). Four participants’ %SS obtained at the time of the study compared to immediately after termination of therapy had increased slightly although this difference was not statistically significant (p = 0.4375). All parents reported that they had noted improvement in their child’s speech since the termination of therapy except for one mother who reported that her child’s speech had remained the same. Conclusions: It would seem that the Lidcombe Programme was successful with this particular group of participants as all of the children demonstrated a definite decrease in stuttering following therapy compared to pre-treatment and had maintained the levels of fluency obtained post-treatment to the time of the study. These findings have implications for early communication intervention, training of speech-language pathologists, theory and future research. KEY WORDS: stuttering, Lidcombe Programme, children, severity rating (SR) percentage syllables stuttered (%SS)
STUDENT NO: 9902414P MA HUMANITIES SCHOOL OF HUMAN AND COMMUNITY DEVELOPMENT
Keywords: STUTTERING; LIDCOMBE PROGRAMME; CHILDREN; SEVERITY RATING (sr); PERCENTAGE SYLLABLES STUTTERED; %SS